Sektor Basis Kabupaten Ngawi Berbasis Sistem Informasi Geografis - Widyaningrum, Eka Dyah Ayu; Cahyono, Hendry (Independent: Journal of Economics, 2021)
Map is simply an illustration of an area in which the information given is displayed in symbols. Map is presented to provide information regarding location barriers, infrastructure, and land use. The existence of basic sector mapping in Ngawi District is expected to become a basis in development plant in the district. The present study was conducted using the Location Quotient (LQ) analysis and Shift Share. The data were of Gross Domestic Regional Product Ngawi Regency from 2015-2019, which was obtained from Central Breau of Statistic. The data mapping was analyzed through ArcGis software. The findings demonstrate that the basic sectors in Ngawi District consist of the farming sector, communication and transportation sectors, along with services sectors.